An experimental study on dynamic behaviour of a sandwich beam with 3D printed hexagonal honeycomb core filled with magnetorheological elastomer (MRE). (1st May 2022) - Sharif, Umer; Chen, Lin; Sun, Beibei; Ibrahim, Dauda Sh; Adewale, Orelaja Oluseyi; Tariq, Noman
Abstract: Sandwich beams with an aluminium face sheet and a magnetorheological elastomer (MRE) of varying proportions of elastomer and magnetic particles (weight to weight)% filled in a honeycomb core of Nylon and Resin8000 are manufactured and experimentally analysed in this study. To evaluate the dynamic properties of sandwich beams, manufactured structures subjected to sine sweep and classic shock tests and assessed both with and without magnetic field of varying intensities applied on the free end of the beam. The experimental results demonstrated good performance in vibration level attenuation, particularly in the structure's primary vibration mode under consideration. The magnetic field applied was capable of lowering the first natural frequency of the proposed sandwich beam structures. Experiment results showed that an increase in an induced magnetic field shifted the natural frequencies, vibration amplitude, and damping ratio of sandwich panels with MRE honeycomb core.